PENGARUH HARGA, KUALITAS PRODUK, DAN WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN MINUMAN KOPI (STUDI PADA KONSUMEN DI SEKALA COFFEE MADIUN) - Okky Ihzan Satria Pramurdjito; Nuriah Yuliati; Dona Wahyuning Laily (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2023)
The development of coffee consumption has also encouraged many new coffee shop businesses to emerge. So that it results in competition in the coffee shop business. This has led to a decline in sales experienced by Sekala Coffee Madiun. The goal of this study was to examine how consumers at the Sekala Coffee Madiun choose their coffee beverages based on price, product quality, and word-of-mouth recommendations. All customers who had purchased coffee beverages at Sekala Coffee Madiun comprised the study's population. Meanwhile, the sample used in this research was 75 people who had bought coffee drink products at Sekala Coffee Madiun. The method of sampling employed the Accidental sampling method. In this study, primary data and secondary data were collected. The data analysis method used in this research is component-based Structural Equation Model (SEM) analysis using PLS which was chosen as the analysis tool with the help of the SmartPLS 3. The study's findings suggested that the price variable has no impact on consumers' choices. Meanwhile, the product quality variable has a significant influence on purchasing decisions. Likewise, the word-of-mouth variable has an influence and is significant on purchasing decisions. Key words:   Price, Product Quality, Word of Mouth, Decision to Purchase.